2017
DOI: 10.1080/09513590.2017.1404235
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic role of vitamin D deficiency in the development of menstrual dysfunction in pubertal girls: a literature review

Abstract: In the literature review, 50 scientific sources surrounding the problem of vitamin D deficiency, 80% of which amounted to the issuance of the last 5 years, have been analyzed. Despite the impact of vitamin D deficiency on the health of children and adolescents has been studied for a long time, the information on the role of vitamin D in the formation of menstrual function in pubertal girls is scant and ambiguous. Among the hypotheses of menstrual dysfunction with vitamin D deficiency, neurohumoral regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(28 reference statements)
0
7
0
2
Order By: Relevance
“…The VDR polymorphism and the subsequent Vit. D deficiency [ 28 , 29 ] or defective action [ 30 , 31 ] was reported with different female reproductive disorders [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VDR polymorphism and the subsequent Vit. D deficiency [ 28 , 29 ] or defective action [ 30 , 31 ] was reported with different female reproductive disorders [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review (containing retrieved data from 50 scientific sources) reported an association between Vit. D deficiency and different pubertal menstrual dysfunctions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Найчастіше описується статус ВD у пацієнток із синдромом полікістозних яєчників, ендометріозом, лейоміомою матки, а також його рівень пов'язують із результатом екстракорпорального запліднення [14][15][16][17]. Незважаючи на те що статус ВD у дітей і підлітків вивчається багатьма дослідниками, його вплив на формування менструальної функції та її порушення в періоді пубертату вивчений недостатньо, про що свідчать поодинокі роботи [18,19]. Разом із тим необхідні дослідження з вивчення рівня ВD для підтвердження його ролі у формуванні порушень менструальної функції, особливо в підлітковому віці.…”
Section: вступunclassified
“…Vitamin D receptors are present in many cells, with otherwise regulated functions and in these cases calcitriol has a side-regulator role [17,18]. The classification of "vitamin" D is faulty, as it is a hormone, with regular receptor in the steroid (nuclear) receptor superfamily in which used to be overlaps between the receptors, considering the hormones and binding specificity of receptors [19,20].…”
Section: Two Vitamins Which Are Exohormones Vitamin Dmentioning
confidence: 99%